Queen's Wharf, Trinidad. - (:unkn) unknown (My University, 2011)
A picture of Queen's Wharf, Port of Spain Trinidad. In this picture you can see the lighthouse and customs office as well as people standing by the waters edge, near floating row boats. In the background there are other buildings.
Colour: Black and White; Style: Landscape; Other: Bordered.
Keywords: Trinidad and Tobago; Postcards; [1925]; Cities and towns--Trinidad and Tobago--Port of Spain; Lighthouses--Trinidad and Tobago; Docks--Trinidad and Tobago; Harbors--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Ports of entry--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Mountains--Trinidad and Tobago